Capturing Technology for Development : An Evaluation of World Bank Group Activities in Information and Communication Technologies, Volume 1. The Evaluation - Independent Evaluation Group (Washington, DC: World Bank, 2012)
Technological innovation drives economic progress. Information and communication technologies (ICT) can be leveraged for development, but harnessing this potential depends on an enabling environment for their production, diffusion, and use. Otherwise, technology can widen rather than narrow existing inequalities. Over the past decade developing countries have seen rapid but uneven growth in ICT access and use. The unprecedented spread of mobile technologies, driven by private sector investment and supported by reforms to promote competition, enabled the growth of phone services for the underserved and poor to levels unseen before. But outside mobile telephony, large gaps exist in high-speed Internet access and broadband connectivity and in the diffusion and use of ICT in business, services, and government the areas where ICT can deliver the largest developmental impacts. The World Bank Group's strategy has sought development results in ICT by promoting (i) sector reform, (ii) access to information infrastructure, (iii) ICT skills development, and (iv) ICT applications. Among these areas, the Bank Group's most notable contributions have been in sector reforms and support to private investments for mobile telephony in difficult environments and in the poorest countries, where most of its activities have taken place. Countries with Bank Group support for policy reform and investments have increased competition and access faster than countries without such support. Going forward, the World Bank Group should retain a role in ICT, but with an important shift in priorities. First, the importance of reforms suggests a role for the Bank in this area related to (i) updating regulatory frameworks and (ii) preserving competition in the face of consolidation and convergence in the sector. Second, gaps in broadband and internet access, in the context of overall expansion of coverage, call for a selective role of the International Finance Corporation (IFC) and the Multilateral Investment Guarantee Agency (MIGA) in supporting private investments in difficult environments.